Probabilistic Reversal Learning Deficits in Patients With Methamphetamine Use Disorder—A Longitudinal Pilot Study - Pilhatsch, Maximilian; Pooseh, Shakoor; Junke, Alexandra; Kohno, Milky; Petzold, Johannes; Sauer, Cathrin; Smolka, Michael N. (Frontiers in Psychiatry, 2020)
Methamphetamine use disorder (MUD) is increasing worldwide and commonly associated with learning deficits. Little is known the about underlying trajectories, i.e. how the affected higher order cognitive functions develop over time and with respect to abstinence and relapse. A probabilistic reversal learning (PRL) paradigm was implemented to uncover the microstructure of impulsive choice and maladaptive learning strategies in 23 patients with MUD in comparison with 24 controls. Baseline data revealed fewer optimal choices and a pattern of altered learning behaviour from negative and positive feedback in patients suggesting impairments in flexibly adapting behaviour to changes of reward contingencies. Integrating longitudinal data from a follow-up assessment after 3-months of specific treatment revealed a group-by-time interaction indicating a normalization of these cognitive impairments in patients with MUD. In summary, our study demonstrates behavioural correlates of maladaptive decision-making processes in patients with MUD, which may recover after three months of MUD-specific therapy paving the way for further learning-based interventions. Limited by a small sample size, the results of this pilot study warrant replication in larger populations.